A‐ and B‐site Codoped SrFeO3 Oxygen Sorbents for Enhanced Chemical Looping Air Separation. Issue 2 (12th December 2019) - Dou, Jian; Krzystowczyk, Emily; Wang, Xijun; Robbins, Thomas; Ma, Liang; Liu, Xingbo; Li, Fanxing
Abstract: Chemical‐looping air separation has numerous potential benefits in terms of energy saving and emission reductions. The current study details a combination of density functional theory calculation and experimental efforts to design A‐ and B‐site codoped SrFeO3 perovskites as "low‐temperature" oxygen sorbents for chemical‐looping air separation. Substitution of the SrFeO3 host structure with Ca and Co lowers oxygen vacancy formation energy by 0.24–0.46 eV and decreases the oxygen release temperature. As a result, Sr1− x Ca x Fe1− y Co y O3 (SCFC; x= 0.2, 0.0< y <1.0) spontaneously releases oxygen at 400–500 °C even under a relatively high oxygen partial pressure (e.g. P O 2 =0.05 atm). Sr0.8 Ca0.2 Fe0.4 Co0.6 O3 exhibits a significantly higher oxygen capacity of 1.2 wt % at 400 °C and under a P O 2 swing between 0.05 and 0.2 atm, when compared to the <0.2 wt % capacity for undoped a SrFeO3 (SF) and Ca‐doped Sr0.8 Ca0.2 FeO3 (SCF). Electrical conductivity relaxation (ECR) study demonstrates that codoping of Ca and Co lowers the activation energy of oxygen diffusion and surface oxygen exchange by 26.6 or 137.9 kJ mol −1, respectively, resulting in faster redox kinetics for SCFC than for SCF perovskite. The SCFC oxygen sorbent also exhibits excellent stability for 2000 redox cycles for air separation. Abstract : Different CLAS : A‐ and B‐site codoping effectively promotes SrFeO3 ‐based oxygen sorbents for low temperature chemical‐looping air separation. Codoping of Ca and Co not only reduces oxygen vacancy formation energy but also lowers energy barrier for oxygen diffusion and surface oxygen exchange, leading to >1 wt % oxygen capacity at 400 °C and fast redox kinetics.